Intermolecular Inter-ligand Interaction in Mixed Ligand Complexes of Lanthanides(III) Involving Histidine and Some Amino Acids - Tiwari, Vivek; Singhai, Rashmi (Asian Journal of Chemistry, 2010)
The formation constant studies on binary and mixed ligand complexes of Pr(III) and Nd(III) involving histidine (hist) as primary ligand and α-alanine ( α-ala), valine (val) or leucine (leu) as secondary ligands have been undertaken to evaluate the extra-stablization in the mixed ligand complexes due to possible occurrence of intramolecular inter-ligand interaction. Stability quantifying parameters ( Δlog k and ΔΔ log k) indicate significant inter-ligand interaction.